(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents a comprehensive assessment of the diagnostic capabilities of multislice computed tomography (MSCT) of the thoracic organs and an analysis of the dosimetric characteristics of ionizing radiation. It discusses issues of radiation prevention, optimization of scanning parameters, and enhancement of diagnostic informativeness while reducing radiation exposure. A review of modern low-dose MSCT technologies, image reconstruction methods, and dose correction algorithms is provided. The study substantiates the high diagnostic value of MSCT in detecting lung, mediastinal, and thoracic wall pathologies.